Experimental Study on Influence of Vaporous Water on Salt Expansion of Sulfate Saline Soil - Shuquan Peng; Fan Wang; Ling Fan (Advances in Civil Engineering)
The harm of salt expansion of saline soil in arid areas has always been a major problem to be solved urgently. According to the conversion rule between sodium sulfate and sodium sulfate decahydrate, sodium sulfate decahydrate crystals can be precipitated from sodium sulfate solution by cooling. Besides, when the relative humidity (RH) exceeds the critical relative humidity (CRH), sodium sulfate decahydrate can be formed by the combination of sodium sulfate and vaporous water, resulting in the salt volume expansion. However, at present, in the salt expansion mechanism of sulfate saline soil, only the influence of liquid water is considered while vaporous water is not involved. To study the effects of temperature, salinity, and ARH on salt expansion, the salt expansion test of dry sulfate saline soil under the action of vaporous water was conducted, and its composition was analyzed by X-ray diffraction (XRD) technology. Experimental results showed that sodium sulfate decahydrate crystals were produced in the sulfate saline soil if the relative humidity (RH) of pore gas exceeded the critical one so that salt expansion occurred. Salt expansion and salt expansion rate of sulfate saline soil increased with the increase of RH and salinity but decreased with the increase of temperature. Therefore, the new salt expansion mechanism of sulfate saline soil under vaporous water is verified. The experimental results further perfected the original salt expansion mechanism of sulfate saline soil under the action of liquid water and guided the study of new treatment methods of sulfate saline soil.